The Effect of Games Simulation in Improving Secondary Students' Academic Performance - Dorji, Tshewang (International Journal of Social Learning (IJSL), 2022)
The main purpose of the study was to find out the effect of simulation games as an intervention program in teaching-learning economics to improve students' academic performance. The study adopts a mixed method. 27 (14 girls and 13 boys) grade twelve students in one higher secondary school participated in the study. The students were selected through non-probability convenient sampling techniques. The study revealed that the intervention program: and simulation games make concepts, ideas, and hypotheses easier to understand. The students have a positive opinion of simulation games used in teaching-learning. Simulation games make teaching-learning interesting, enjoyable, and fun. Through simulation games, students can score high marks on the class test. Students were engaged in self-assessment, self-awareness, self-monitoring, and reflective processes. However, the study revealed that simulation games are time-consuming and teachers need more time and effort for preparation and implementation. Simulation games are not always effective in teaching all micro and macroeconomics concepts.